Image Encryption Method Using New Concept of Compound Blood Transfusion Rule with Multiple Chaotic Maps - Gupta, Ranu; Pachauri, Rahul; Singh, Ashutosh K. (Current Medical Imaging, 2020)
Introduction: With the advancement in internet technology, a large amount of information in the form of data and image is transferred from one end to the other. The information may be military, defense, medical, etc. which should be kept confidential by providing security. Objective: The aim of this article will be to provide security to the image. This is achieved by applying the image encryption method which converts the original information into an unreadable format. Methods: This work explores an efficient way of image encryption using a chaotic logistic function. A set of two chaotic logistic functions and 256 bit long external secret key are employed to enhance the security in the encrypted images. The initial condition of first logistic function has been obtained by providing the suitable weights to all bits of the secret key. The initial condition of second logistic function has been derived from the first chaotic logistic function. In this proposed algorithm, ten different operations are used to encrypt the pixel of an image. The outcome of the second logistic map decides the operation to be used in the encryption of the particular image pixel. Results: Various statistical parameters like NPCR, UACI and information entropy were calculated. Conclusion: Results show that the proposed algorithm provides an image encryption method with better security and efficiency for all real-time applications such as medical images.
Keywords: encryption